Tugan‑Baranovsky and the West - François Allisson (Russian Journal of Economics, 2021)
Mikhail Tugan‑Baranovsky was one of the most prolific Russian economists at the turn of the 19–20th centuries. His thought was largely influenced by Western ideas, like most of his fellow Russian economists. But Tugan‑Baranovsky’s theories in turn also influenced Western economic thought to an unprecedented extent. Tugan‑Baranovsky’s Western legacy is first reflected on, before we examine the West’s reception of two of his works: “Industrial crises in England” (1894) and “Theoretical foundations of Marxism” (1905). We compare the conception of these works vis-à-vis their intended audience, and their reception in the international context of the circulation of ideas, so as to define Tugan‑Baranovsky’s relationship with the West.